Psychometric Properties of the Chinese Version of the Premonitory Urge for Tics Scale: A Preliminary Report - Li, Ying; Woods, Douglas W.; Gu, Yi; Yu, Liping; Yan, Junjuan; Wen, Fang; Wang, Fang; Liu, Jingran; Cui, Yonghua (Frontiers in Psychology, 2021)
Premonitory urges (PUs) are sensory phenomena that immediately precede tics. The Premonitory Urge for Tics Scale (PUTS) is widely used to assess the severity of PUs, but the psychometric properties of PUTS and clinical features of PU in Chinese patients with tic disorders are still unclear. In this study, we examined the psychometric properties of the Chinese version of the PUTS in a large sample (including 367 Chinese pediatric patients with tic disorders). We found no difference in PU in different age groups. The exploratory factor analysis of PUTS showed the emergence of four primary factors. The results of reliability and validity analyses indicated that the Chinese version showed good psychometric properties. It seemed that PU was associated with the severity of obsessions symptoms in patients with tic disorders. Network analysis showed that Item 7 is a critical node for the PU, in addition to Items 1 and Item 4. Overall, the Chinese version of PUTS can be used in Chinese child and adolescent patients with tic disorders, particularly for TS patients.